Synthesis of Isoxazolylvinyl Ketones from Substituted Furans - Serdyuk, Olga; Hampel, Frank; Abaev, Vladimir T. (Chemistry of Heterocyclic Compounds, 2020)
[Figure not available: see fulltext.] A new method for the preparation of isoxazolylvinyl ketones related to potential cytotoxic agents has been developed. In the first step, the reaction of furfuryl ketones with hydroxylamine hydrochloride affords the corresponding oximes. Further, the oxidative ring opening – ring closure reaction of oximes leads to isoxazoles with an α, β-unsaturated carbonyl motif. The developed procedure is metal-free and does not require expensive starting materials.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chalcone; furan; isoxazole; ring opening – ring closure reaction